1998
DOI: 10.1038/sj.leu.2400893
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotypic patterns and cytogenetic anomalies in acute non-lymphoblastic leukemia subtypes: a prospective study of 432 patients

Abstract: This study prospectively analysed the relationships between observed to vary according to the type and number of lymphimmunophenotypic and cytogenetic features of blast cells in oid lineage antigens expressed. 9 The expression of some of 432 acute non-lymphoblastic leukemias (ANLL) at presentation.these antigens also appeared to be related to recurrent cyto- The study was initiated in March 1992 by the Groupe d'Etude Immunologique des Leucémies (GEIL), a French multicentric Introduction group that collects da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 6 publications
1
32
0
Order By: Relevance
“…Indeed, in non-M3 subtypes, 73.1% of CD34-positive patients had chromosome abnormalities. Although some reports failed to find the correlation between CD19 expression and the presence of t(8;21) in M2 cases (1), our results also further support the well-recognized knowledge that the expressions of CD15, CD19, CD34, and CD56 were significantly increased in AML with t(8;21) (9)(10)(11). Reports showed that immunophenotyping had a sensitivity of 100% and a specificity of 99% for predicting PML/RARalpha gene rearrangements, and the expression pattern of CD34, CD15, and CD13 was highly characteristic of the presence of it (2).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Indeed, in non-M3 subtypes, 73.1% of CD34-positive patients had chromosome abnormalities. Although some reports failed to find the correlation between CD19 expression and the presence of t(8;21) in M2 cases (1), our results also further support the well-recognized knowledge that the expressions of CD15, CD19, CD34, and CD56 were significantly increased in AML with t(8;21) (9)(10)(11). Reports showed that immunophenotyping had a sensitivity of 100% and a specificity of 99% for predicting PML/RARalpha gene rearrangements, and the expression pattern of CD34, CD15, and CD13 was highly characteristic of the presence of it (2).…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies suggested that several antigens such as CD34, CD56, and TdT on AML cells were highly related to abnormal chromosome karyotype, but the patients found with cytogenetic changes were mostly lacking special immunophenotypes (9,10). Our study showed that about 54.1% of AML had at least one type of chromosome change.…”
Section: Discussionmentioning
confidence: 52%
“…Recent utilization of molecular testing has led to the identification of PML-RAR␣ positive variants with atypical morphology [15,33]. Although expression of CD34 was initially considered uncommon [14], recent studies have shown that CD34 positivity occurs in about 20-30% of newly diagnosed cases [12,[20][21][22]. The significance of CD34 expression in APL is unknown but likely identifies an immature form of APL.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, the detection of CD34 in t(15;17) APL was considered infrequent [14]; however, several reports have now shown that expression of CD34 occurs in a significant proportion of newly diagnosed t(15;17) APL patients [12,[20][21][22]. Although CD34 positivity has been associated with a lower rate of complete remission in combined subtypes of acute myeloid leukemia (AML) [23][24][25], the significance of CD34 expression in t(15;17)/ PML-RAR␣ APL is not known.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Progress of diagnostic methods, that is, morphology, cytogenetics, immunophenotyping and molecular biology has led to the identification of prognosis factors [3][4][5] and has helped to better stratify patients. 6 Nevertheless, it is difficult to properly appreciate the efficacy of induction therapy before the first informative examination of bone marrow smears.…”
Section: Introductionmentioning
confidence: 99%